Reassessing Classical Kalam: A Critical Analysis of the Relevance of Islamic Theology in the Age of Globalization - Fuadi, Azrian Isyfaul (Faculty of Teacher Training and Education, Palangka Raya University, Central Kalimantan, Indonesia. Pos Code 73112, 2025)
Islamic theology is a field of study concerned with matters of creed. However, throughout its historical development, classical Islamic theology has been characterized by a predominant focus on metaphysical issues and the vertical relationship between humans and God. The objective of this study is defined as the identification of epistemological weaknesses and the tendency toward stagnation within classical Islamic theology, which is considered irrelevant to the contemporary context. Therefore, the reexamination of classical Islamic theology is deemed necessary so that it may remain relevant to the issues faced by humanity in the present century. A qualitative method with a library research approach is employed in this study. Data analysis is conducted through data reduction, data presentation, and interpretation in order to obtain a comprehensive conceptual understanding. The findings indicate that classical Islamic theology is marked by stagnation due to its excessive emphasis on metaphysical matters, resulting in limited capacity to address social challenges in the era of globalization. Globalization is viewed as necessitating a renewal of theology that is more rational, adaptive, and relevant to societal needs. It is concluded that a contextual and transformative reconstruction of Islamic theology is required. The concept of ummatan wasathan is presented as offering a foundation for the development of a moderate theology that is responsive to contemporary change. The implications suggest that Islamic theology needs to be directed toward a form of social theology capable of addressing issues such as poverty, injustice, and identity crises. Teologi Islam merupakan bidang kajian yang membahas persoalan akidah. Namun dalam perkembangan sejarahnya, teologi Islam klasik lebih banyak berfokus pada persoalan metafisik dan hubungan vertikal antara manusia dengan Tuhan. Tujuan dari penelitian ini adalah untuk mengidentifikasi kelemahan epistemologis dan cenderungnya stagnasi dalam teologi Islam klasik yang tidak relevan dengan konteks saat ini. Oleh sebab itu, teologi Islam klasik butuh dikaji kembali agar relevan dengan persoalan manusia abad ini. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan (library research), Analisis data dilakukan melalui reduksi data, penyajian data, dan interpretasi untuk memperoleh pemahaman konseptual yang komprehensif. Penelitian ini menemukan bahwa teologi Islam klasik cenderung stagnan karena terlalu berfokus pada persoalan metafisik sehingga kurang mampu menjawab tantangan sosial di era globalisasi. Globalisasi menuntut pembaruan teologi yang lebih rasional, adaptif, dan relevan dengan kebutuhan masyarakat. Penelitian ini menyimpulkan perlunya rekonstruksi teologi Islam yang kontekstual dan transformatif. Konsep ummatan wasathan menawarkan landasan bagi pengembangan teologi moderat yang responsif terhadap perubahan zaman. Implikasinya, teologi Islam perlu diarahkan menjadi teologi sosial yang mampu menangani persoalan kemiskinan, ketidakadilan, dan krisis identitas.